The Effect of Transformational, Transactional, and Laissez-Faire Leadership Styles on Employees’ Level of Performance: The Case of Hospital in Oromia Region, Ethiopia - Hundie ZA; Habtewold EM (Dove Medical Press, 2024)
Zeleke Amena Hundie, Ephrem Mannekulih Habtewold Deparment of Public Health, Adama Hospital Medical College, Adama, EthiopiaCorrespondence: Zeleke Amena Hundie, Tel +251911617412, Email amenazeleke27@gmail.comPurpose: Poor performance of health service providers has a negative impact on the ability of health systems to produce desired outcomes. Lack of suitable and impactful leadership hinders employee performance in terms of providing a high standard of care. There is a paucity of evidence on the effect of leadership style on employee performance in the current study setting. Hence, this study sought to assess the effect of leadership styles on employee performance in hospitals in the Oromia region, Ethiopia, from August 1 to October, 30, 2021.Methods: A cross-sectional study was conducted using a sample of 41 hospitals and 412 employees, selected by stratified sampling from hospitals in the Oromia region. The data were collected using self-administered questionnaires. They were then coded and entered into the Epi-Info-7.2. software, and exported to SPSS-20 for analysis. The participants' characteristics were analyzed and summarized using descriptive statistics. Employee performance was rated as low, average or high, and estimated by proportion along with a 95% confidence interval (CI). The association between leadership styles and the level of employee performance was modelled using ordinal logistic regression. The magnitude of association was estimated by odds ratio with a 95% CI. Statistical significance was set at p < 0.05.Results: Employees had an increased odds of being a high performer when they experienced the following leadership styles: transformational with idealized influence (AOR=1.70; 95% CI: 1.12, 2.64), intellectual stimulation (AOR=1.60; 95% CI: 1.04, 2.48), laissez-faire approach (AOR=2.49; 95% CI: 1.71,3.62), effectiveness in terms of frequently fulfilling employees' job-related needs (AOR=2.09; 95% CI: 1.20,3.63), and the exertion of extra effort in motivating them (AOR=2.11; 95% CI: 1.22, 3.68).Conclusion: Among leadership styles, transformational with idealized influence and intellectual stimulation, laissez-faire approaches were significantly associated with employee performance. However, transactional leadership was not significantly associated with employee performance.Keywords: employee performance, Ethiopia, hospital, Oromia, leadership styles